STUDI DAYA TARIK CALON LOKASI EKOWISATA AIR MERAH DI DUSUN MUNGGUK KECAMATAN NGABANG KABUPATEN LANDAK - Kurniawan, Nikolaus; Said, Syafruddin; anto, Eri (Universitas Tanjungpura, 2013)
Air Merah is one of the candidate sites Ecotourism potentially high natural and other natural beauty, as a candidate region ecotourism destination, Red Water has its own characteristics (special interest) as local ceremonies and socio-economic life. This study was conducted to obtain data on the value of appeal contained in the Red Zone Air Travel for tourism development in particular in the hamlet Kab'Landak Mungguk. The method used was a descriptive analytic, ie with the intention of explaining all potential objects of research that has been observed and analyzed by using standard observation guidelines Raw Size or Standard Assessment and Development of Natural Attraction. Assessment consists of natural beauty, unique natural resources, natural resources stand, the integrity of natural resources, sensitive natural resources, choice of leisure activities, hygiene and local air and space for visitors. Based on the results of the overall study that assessed element of attraction, then after summed value of 123.15. This value is multiplied by the weighting criteria appeal to the area that is 6, so the value for the area of ??regional attractiveness criteria Ecotourism Air Merah to 123.15 X 6 = 738.9, as compared with the Classification element Object Development Ecotourism Nature Air, the area Red area has an appeal that is being (D) to be developed into a natural tourist attraction. Air Merah has good prospects in the development of nature tourism in the future, especially when supported interactive cooperation between the government, public, and private parties / investors, so the need for the determination of the status of the region and the juridical protection of the local government in order to protect against potential appeal in the Air Merah. Key word : Ecotourism, attractiveness value, nature, Air Merah